Treatment of a medial plica in the knee among German knee surgeons – The Plica Survey - Svea Faber; Philipp W. Winkler; Ralf Henkelmann; Theresa Diermeier; Wolf Petersen; Maurice Balke; Sebastian Metzlaff; Sebastian Colcuc; Gerald Zimmermann; Philip P. Roessler; Thomas R. Niethammer (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology)
Purpose: The MPP (medial patella plica) has garnered increasing clinical attention due to its potential role in patellofemoral pain syndromes. While often an anatomical relic without pathological significance, inflammation or mechanical irritation of this structure can lead to plica syndrome, causing significant clinical symptoms. The purpose of this study was to analyze the current care situation regarding plica syndrome of the knee among a large number of experienced knee surgeons. Methods: An online survey targeting the current care practices for plica syndrome was conducted among members of the German Knee Society (DKG). The survey was comprised 15 questions regarding diagnostic and treatment approaches. Data were collected anonymously and analyzed using IBM SPSS Statistics Version 26.0. Results: A total of 238 surgeons participated. Most respondents (84 %) agreed that plica syndrome could cause patellofemoral pain. The typical patient profile was predominantly female (77.7 %), aged 21–30 years (57.6 %). The majority of surgeons use magnetic resonance imaging (MRI) combined with clinical examination (58.0 %) to diagnose an MPP, and 54.2 % of surgeons resected the plica upon finding significant intraoperative evidence of impact on the patellofemoral joint. Hemarthrosis and persistent pain were the most reported complications, though 83.2 % of surgeons observed a complication rate below 11 %. Conclusion: This study provides a comprehensive overview of current practices and opinions regarding plica syndrome among experienced German knee surgeons. It emphasizes the need for further research to standardize diagnostic and therapeutic approaches, aiming to optimize patient outcomes in plica-related knee pathologies.